(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The potential impact of the peripheral refraction on the refractogenesis and development of myopia is a substantiation for using orthokeratologic therapy to form a peripheral myopic defocus in patients with myopia. Purpose. To study the long-term results of orthokeratologic therapy in patients with myopia. Material and methods. 21 patients (42 eyes) with myopia from -0.75 D to -4.5 diopters who used the night contact lenses Paragon CRT 100 were followed up for 3 years. Results. The long-term results of ortokeratologic therapy showed the positive effect on slowing of the myopic process. Conclusion.The most positive effect of ortokeratologic therapy was observed in patients with refractive component due to the curvature of the cornea.